The Effect of Internet-Based Cognitive Behavioral Therapy on Major Depressive Disorder: Randomized Controlled Trial - Ziyi Lin; Lu Cheng; Xue Han; Hongqiong Wang; Yuhua Liao; Lan Guo; Jingman Shi; Beifang Fan; Kayla M Teopiz; Muhammad Youshay Jawad; Huimin Zhang; Yan Chen; et al. (JMIR Publications, 2023)
BackgroundMany people living with major depressive disorder (MDD) in China do not receive treatment owing to a lack of mental health services, along with significant stigma toward mental illness. Internet-based cognitive behavioral therapy (ICBT) has been proposed to increase access to mental health care for people with MDD. ObjectiveThe aims of this study were to (1) evaluate the efficacy of ICBT for depressive symptoms in patients with MDD; (2) evaluate the effect of ICBT on anxiety symptoms, nonspecific psychological distress, general self-efficacy, depression stigma, social function, and health-related quality of life (HRQoL); and (3) explore the acceptability of and satisfaction with the ICBT program among participants. MethodsPatients with MDD were enrolled and randomized to the ICBT group or the waiting-list control (WLC) group. The ICBT group received ICBT delivered through a WeChat mini-program with general support by nonspecialists. Participants in the 2 groups were self-evaluated online at baseline and posttreatment for changes in the primary outcome (ie, depressive symptoms) and secondary outcomes (ie, anxiety symptoms, nonspecific psychological distress, general self-efficacy, depression stigma, social functional impairment, and HRQoL). Changes in outcomes were measured by changes in overall scores on respective scales, and response and remission rates were calculated based on depressive symptoms. The acceptability of and satisfaction with the ICBT program were measured by treatment adherence and participants' feelings (ie, modules seriously completed, perceived benefit, and satisfaction). ResultsWe included 40 patients who were randomly assigned to the ICBT group and 44 who were assigned to the WLC group. Compared with the WLC group, the ICBT group had fewer depressive symptoms, fewer anxiety symptoms, less nonspecific psychological distress, and greater general self-efficacy. Moreover, the ICBT group had higher response (18/31, 58%) and remission rates (17/31, 55%). The adherence rate in the ICBT group was 78% (31/40), and the majority of participants who completed all ICBT modules were satisfied with the ICBT program. ConclusionsICBT demonstrated greater improvements in depressive symptoms, anxiety symptoms, nonspecific psychological distress, and general self-efficacy among selected patients with MDD in comparison with the findings in waiting-list controls. The ICBT program in this study had good acceptability and satisfaction among participants. Trial RegistrationChinese Clinical Trial Registry (ChiCTR2100046425); https://tinyurl.com/bdcrj4zv